Potential COVID-19 Immunomodulators and Beyond: NSAIDs Might Inhibit SARS CoV-2 ORF Proteins Induced Caspase Activation, Necroptosis and Endoplasmic Reticulum Stress. - Mina Kelleni (2021)
Updated, peer reviewed and published https://link.springer.com/article/10.1007/s10787-021-00896-7#Sec7 We have previously suggested numerous immunomodulatory and anti-inflammatory benefits when NSAIDs are administered as first choice therapy early in management of COVID-19 and in this manuscript we add several additional clues and it is really unfortunate that for more than one year of relentless struggle, this call is not yet adopted to save precious lives that are succumbed every day.